2006
DOI: 10.1039/b517199g
|View full text |Cite
|
Sign up to set email alerts
|

C 1s → π* excitation in variable size benzene clusters

Abstract: The C 1s -->pi* transition in molecular benzene and benzene clusters is investigated by photoion yields at high energy resolution. The vibrationally resolved band shows the same shape in clusters as in the bare molecule, but it is redshifted by 50 meV in small clusters, i.e. near the threshold of cluster formation. This redshift increases to 70 meV with increasing cluster size. The results are assigned in comparison with ab initio calculations on model structures of dimers, trimers, and tetramers. These indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 55 publications
9
64
0
Order By: Relevance
“…From a CNT perspective, this research direction reveals the nature of the building units of the [86,88] 5-fluorouracil (nitromethane/water) molecular modeling yes (exp. XPS studies of core-level binding energies associated with hydrogen bonding and protonation have already been carried out [72][73][74][75][76][77][78]97] and together with previous studies of core-level shifts caused by van der Waals and dipole interactions [98][99][100] have prepared the ground for more detailed structural studies of solute-solvent interactions, self-association, and cluster formation. [94] benzophenone (methanol, toluene) NMR yes [91] diphenylamine (methanol, toluene) NMR yes [91] p-acetanisidide (chloroform) NMR yes [84] isonicotinamide (methanol, nitromethane) FTIR, Raman yes [89] carbamazepine (methanol, chloroform) NMR yes [105,106] nucleus, and the nature of the building units is related to the attachment frequency of the molecules.…”
Section: Challenges For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…From a CNT perspective, this research direction reveals the nature of the building units of the [86,88] 5-fluorouracil (nitromethane/water) molecular modeling yes (exp. XPS studies of core-level binding energies associated with hydrogen bonding and protonation have already been carried out [72][73][74][75][76][77][78]97] and together with previous studies of core-level shifts caused by van der Waals and dipole interactions [98][99][100] have prepared the ground for more detailed structural studies of solute-solvent interactions, self-association, and cluster formation. [94] benzophenone (methanol, toluene) NMR yes [91] diphenylamine (methanol, toluene) NMR yes [91] p-acetanisidide (chloroform) NMR yes [84] isonicotinamide (methanol, nitromethane) FTIR, Raman yes [89] carbamazepine (methanol, chloroform) NMR yes [105,106] nucleus, and the nature of the building units is related to the attachment frequency of the molecules.…”
Section: Challenges For Future Researchmentioning
confidence: 99%
“…Dielectric spectroscopy is an emerging technique that reveals information about molecular movement during crystallization from the amorphous state, [95,96] whereas spectroscopic methods with soft X-rays, such as XPS and NEXAFS, have been shown to be sensitive to bond lengths, coordination numbers, and the geometric arrangement of coordinating species, as well as the oxidation and charge state of solute species. XPS studies of core-level binding energies associated with hydrogen bonding and protonation have already been carried out [72][73][74][75][76][77][78]97] and together with previous studies of core-level shifts caused by van der Waals and dipole interactions [98][99][100] have prepared the ground for more detailed structural studies of solute-solvent interactions, self-association, and cluster formation.…”
Section: Challenges For Future Researchmentioning
confidence: 99%
“…Compared to the van der Waals-bonded case of N 2 discussed above, the inter-molecular bonding is stronger for benzene, which is a liquid at NTP. Consequently, the corresponding XAS spectra exhibit somewhat larger, but still small, changes from monomer to cluster than N 2 clusters [104]. The results were assigned in comparison with ab initio calculations on model structures of dimers, trimers, and tetramers.…”
Section: Article In Pressmentioning
confidence: 99%
“…It is known in the previous work that the aromatic π-π interactions cause an energy shift of the π* peak in XAS. [67][68][69] We have also measured C K-edge XAS spectra of benzene clusters in the gas phase, 70 which are formed by an adiabatic gas expansion method, and solid benzene at -193 C, 71 and found that the π* peaks show lower energy shifts compared to those of gas, which is ascribed to different structural properties of clusters compared to the solid. In the present work, we have systematically investigated temperature-dependent changes of ordered structures in liquid benzene by C K-edge XAS with the combination of the MD simulation and inner-shell calculations.…”
Section: •2 Temperature-dependent Structural Changes In Liquidmentioning
confidence: 99%